The Role of Literary Reading in the Context of Digitalization - Adham, Sattarov; Tuychiyevna, Razikova Lola (Research Parks Publishing LLC, 2023)
The article discusses the role of literary reading in the context of digitalization. Reading, being a key skill of an educated person, is being transformed in some way in modern conditions. It is important to determine what changes are taking place in this key skill, because understanding the surrounding reality, the ability to consciously master information is especially important in times of increasing information availability. Opinion is being studied students studying in the direction of medical education. The opinions of the respondents expressed in the essay on the topic